The economic case for developing HVDC-based networks to maximise renewable energy utilisation across Europe: An advanced stochastic approach to determining the costs and benefits - Houghton, Tom; Bell, K.; Doquet, M. (2012)
This paper is concerned with the rationale for development of significantly enhanced transmission capacity on a continent scale, in this case in Europe. With a particular emphasis on the accommodation of wind power in the North Sea, it describes an assessment of the extent to which lack of transmission capacity at a European level will act as a constraint to realising Europe-wide targets for electricity from renewable sources in 2020. A plausible generation and demand scenario has been postulated and inter-area power flows studied in a number of network cases for the whole of Europe. The network cases are intended to provide insights into the drivers for different levels of transmission expansion and the different network configurations by which increased transfer capability might be delivered offshore. The analytical methods used take account of realistic time series of available generation including wind and hydro, model spatial correlations of wind and hydro power, minimum stable generation and on and off times, and regionally differentiated reserve requirements. Most particularly, by means of Monte Carlo simulation, the variability of power deficits and surpluses at different locations and flows between locations can be assessed. The analysis is achieved through use of the ANTARES tool developed by RTE. The main metrics used to compare the different scenarios are annual energy production from different types of generator, emissions of carbon dioxide, the total energy from renewables, and the volume of 'spilled' wind energy. The results suggest that new offshore network capacity to allow increased exchange of power between different countries will be important to realising the full potential of new wind power developments. This new network capacity not only allows local surpluses of wind power to be used elsewhere but also facilitates reserve power to be held remote from a particular area and so minimise the total holding of reserve and increase the utilisation of renewable energy. However, it has two further effects: depending on the exact location, it can permit onshore network constraints to be bypassed and, as is shown, it can allow cheap high carbon generation in remote areas to be used instead of lower carbon fossil fuelled plant in a local area. It may thus be concluded that not only are support for investment in very low carbon generation capacity such as wind and development of the transmission network important for reduction of carbon emissions associated with use of electricity, but so too is effective pricing of carbon emissions.